Nest-site fidelity and breeding dispersal by Common Tailorbirds in a tropical forest - Changzhang Feng; Canchao Yang; Wei Liang (Avian Research, 2019)
Abstract Background Information pertaining to nest-site fidelity and breeding dispersal over successive years can help to better our understanding of how birds respond to nest predation. Methods By using mist nets and tracking the color banded individuals, we investigated nest-site fidelity and breeding dispersal by Common Tailorbirds (Orthotomus sutorius) throughout a year and between successive years in 2017–2018. Results The present study showed that Common Tailorbirds could produce up to four clutches per breeding season. When multiple broods were produced within a year, breeding pairs remained together, and the nest rebuilding rate was up to 92.2%, with only four cases (7.8%) in which birds reused their old nests. The dispersal distance between the nests during multiple breeding was found to be 10.0 ± 10.5 m, and nest-site fidelity within the same year was 90.0%. By the second year of breeding, 76.2% of individuals remained in the original breeding pairs, while for those that did switch partners, the females remained in the nest from the previous year and paired with new males. The dispersal distance between years was 26.5 ± 41.9 m, and nest-site fidelity between different years was 80.1%. There was no significant difference between within-year and between-year dispersal distances. Moreover, there was no significant difference in the dispersal distance of rebuilt nests between birds that had experienced nest predation and those that had not. Conclusions Our findings suggest that Common Tailorbirds maintain a high degree of fidelity to mates and nest-sites, and nest predation had no significant effect on territorial changes or breeding dispersal distance between each breeding attempt.